Nghiên cứu chế tạo vật liệu nanocompozit EVA/TiO2 bằng phương pháp trộn nóng chảy - Công, Đỗ Văn; Tuấn, Vũ Mạnh; Thùy Linh, Mai Thị; Huynh, Mai Đức (Vietnam Journal of Chemistry, 2016)
In this research, the nanocomposite based on ethylene vinylacetate copolymer (EVA) and TiO2 nanoparticles was prepared by three different ways including one-step method, two-step method and direct mixing. The mixing process was carried out in melt state in an intermixer Haake at 170 oC, speed rate of 50 rpm and mixing time of 5 minutes. The results obtained from mechanical measurements, thermal gravimetric analysis (TGA) and Field Emission Scanning Electron Microscopy (FESEM) observations showed that one-step method was suitable for the preparation of EVA/TiO2 nanocomposites. The presence of vinyltrimethoxisilane (VTMS) enhanced the adhesion between TiO2 nanoparticles and EVA matrix as well as improved the dispersion of TiO2 nanoparticles in EVA matrix. The addition of TiO2 nanoparticles in the presence of VTMS increased torque values, tensile strength and Young’s modulus of EVA. Keywords. EVA, TiO2, EVA/TiO2 nanocomposites.